Desain dan Fabrikasi Mesin Pengupas Kelapa Sistem Pengupas Bergigi - Yang Fitri Arriyani; Masdani Masdani; Sastra Setiawan; Ego Fernando; Khodad Azizi Costacurta (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
One part of the coconut that can be utilized and has economic value is the coconut husk. The process of peeling coconut coir must be carried out by someone who has certain skills and this process has a fairly high risk of work accidents. The purpose of this study was to design a coconut coir peeling machine to make it easier for workers to strip and to analyze the costs required to operate the machine. This machine can help the process of peeling coconut coir so that the coir can be separated from the coconut shell, can speed up the stripping time, and make the job of peeling coconut coir easier. Making the machine design begins with making an alternative concept for the stripping system, selecting alternative concepts, making a complete design, and the machine manufacturing process. The selection of alternative design concepts is assessed from the economic aspect and the number of components. Parts of the stripping system are designed with teeth so that the coir can be clamped on the toothed shaft and does not experience slip so as to speed up the stripping process. The coconut coir peeling machine consists of 47 component parts with engine dimensions of 960 mm x 400 mm x 1136 mm and uses a 6.5 HP motor with gasoline. The average capacity of the coir peeling machine is 216 pieces/hour. The estimated fixed cost of using the machine is IDR 2,449,440/year, variable costs are IDR 20,855/hour, basic costs are IDR 101.31/piece, and break even points are 6,071.25 pieces/year.